Optical and electrical studies on crystalline tin sulphide - Merdan, M. (1977)
A Fourier transform far infrared spectrometer bas been constructed to perform reflectivity and transmission measurements on small semiconductor samples in the temperature range 10-300 grad. K. Far infrared and Raman spectra selection rules have been obtained by the Correlation method from the factor group analysis of the 5nS subset. Crystals of n- and p- type SnS bave been prepared, and the preparation methods are critically reviewed with reference to the T-p-x diagram. The electrical properties (Hall effect, carrier concentration, Hall mobility and barrier height) are measured for these specimens in the temperature range 40-3000 K. Methods of obtaining electrical contacts to SnS are exhaustively studied. Broadband photoconductivity and photovoltaic measurements are reported on n- and p-type specimens in the spectral range 0.5-2 .1 eV at temperatures from 300 grad. K to 10 grad. K. Band structure and impurity energies are suggested to account for the observed results. The band edge shift with temperature is also measured. Far infrared reflectivity and transmission measurements are made between 300 grad. K and 10 grad. K. in order to determine the lattice vibration frequencies. Kramers-Kroenig analysis and computer fitting routines are used to obtain this information from the reflectivity data. The interlayer forces are compared with those obtained in the isomorphic materials GeS and GeSe. Similar spectroscopic and analytic techniques have also been used to examine the room temperature optical properties of ZnS+Fe (Marmatite).